أسلوب ضرب الأمثال في القرآن الكريم وأثره في استجابة الخطاب الدعوي - مسعي, محمد (University of Eloued جامعة الوادي, 2022)
يهدف هذا الموضوع إلى تبيان سمة من سمات أسلوب ضرب الأمثال في القرآن الكريم وبيان مكانته وأهميته في فضاء الدعوة الإسلامية، كما يسعى أيضا إلى بيان الأثر الدعوي الذي يخلفه هذا الأسلوب في استجابة الخطاب الدعوي الموجه للمدعوين، ومن أجل ذلك جاءت الدراسة مقسمة في العناصر التالية: أولا تحديد المفاهيم ومتغيرات الموضوع، ثانيا: أهمية أسلوب ضرب الأمثال في إيضاح بلاغة الخطاب الديني، والعنصر الثالث والأخير أثر أسلوب ضرب الأمثال في استجابة الخطاب الدعوي ونجاح الدعوة الإسلامية. This subject aimed at clarifying characteristic of The method of multiplication of proverbs in the Holy Quran, And explain its importance and its place In the space of the Islamic call, it also seeks to statement the call impact who successor him in response the call speech addressed fromthe God to the kind invited to the way of Allah, for this reason, the study was divided into the following elements: first, defining the concepts and variables of the subject, second: the importance of the proverbial method in clarifying the eloquence of religious discourse, and the third and final element the impact of the proverbial method in the response of the advocacy discourse and the success of the Islamic call